Desastres, infraestrutura e desenvolvimento: interrupções nas rodovias e impactos ao desenvolvimento na Amazônia - FLORES, Rafael Almeida (Universidade Federal do Pará, 2019)
The development of a region is related, in part, to its ability to establish relations with other regions and the efficiency with which it operates internally and streamlines their intra relations. The study of the impacts in the availability of transport infrastructure in regional development interests by the influence it has on the location decisions of investment. This work describes a systematic, organized and distributed within that shape the relationship between the operation of transport infrastructure and natural disasters impacting regional development. Location data, causes, frequency of events, resulting impacts and potential occurrence of disasters that cause disruptions in the transportation system of the Brazilian Amazon region are presented, explaining how all of this impacts regional. The network of transport infrastructure in the Brazilian Amazon region is susceptible to interruptions in its functioning by pressures arising from the interaction of coupled human and natural systems, impacting regional development mainly by isolating regions raising concerns about human security of local residents and the economic development to the extent that regional production does not circulates temporarily, eliminating one of the economy dynamics main stages. The susceptibility indicators of transport infrastructure system in the Amazon are unclear being here presented temporal data, distributed in the geographic space, in order to describe the Amazonian transportation network scenario in the natural disasters context. This study presents disruptions causes, frequency, potential risks and impacts in this system functioning through an infrastructure disaster impacts evaluation methodology on the case of the BR-364 highway flood study and the respective impact on the 2014 Acre and Rondonia states, demonstrating that even action plans could be the origin element to more impacts, further aggravating the situation, showing a clear lack of the State preparation to deal with natural disasters